Report From the American Society of Transplantation Conference on Donor Heart Selection in Adult Cardiac Transplantation in the United States. Issue 10 (13th June 2017) - Kobashigawa, J.; Khush, K.; Colvin, M.; Acker, M.; Van Bakel, A.; Eisen, H.; Naka, Y.; Patel, J.; Baran, D. A.; Daun, T.; Luu, M.; Olymbios, M.; et al.
Abstract : Cardiac transplantation remains the only definitive treatment for end‐stage heart failure. Transplantation rates are limited by a shortage of donor hearts. This shortage is magnified because many hearts are discarded because of strict selection criteria and concern for regulatory reprimand for less‐than‐optimal posttransplant outcomes. There is no standardized approach to donor selection despite proposals to liberalize acceptance criteria. A donor heart selection conference was organized to facilitate discussion and generate ideas for future research. The event was attended by 66 participants from 41 centers with considerable experience in cardiac donor selection. There were state‐of‐the‐art presentations on donor selection, with subsequent breakout sessions on standardizing the process and increasing utilization of donor hearts. Participants debated misconceptions and established agreement on donor and recipient risk factors for donor selection and identified the components necessary for a future donor risk score. Ideas for future initiatives include modification of regulatory practices to consider extended criteria donors when evaluating outcomes and prospective studies aimed at identifying the factors leading to nonacceptance of available donor hearts. With agreement on the most important donor and recipient risk factors, it is anticipated that a consistent approach to donor selection will improve rates of heart transplantation. Abstract : This meeting report outlines the proceedings of a conference sponsored by the American Society of Transplantation and represents the current donor selection practices of adult heart transplant centers in the United States, a suggested standardized approach to donor selection, and avenues for future research. See the editorial from Smits onpage 2503 .